Changing the narrative on fisheries subsidies reform: Enabling transitions to achieve SDG 14.6 and beyond. (July 2020) - Cisneros-Montemayor, Andrés M.; Ota, Yoshitaka; Bailey, Megan; Hicks, Christina C.; Khan, Ahmed S.; Rogers, Anthony; Sumaila, U. Rashid; Virdin, John; He, Kevin K.
Abstract: The World Trade Organization (WTO) is in the final stages of negotiating an agreement to prohibit harmful fisheries subsidies, thereby achieving UN Sustainable Development Goal (SDG) 14.6. An effective agreement should be viewed as an opportunity for nations to proactively transition towards sustainable and equitable fisheries and pave the path for other SDGs. Supporting fishers does not require harmful subsidies, and we provide evidence-based options for reform that highlight equity needs while reducing environmental harm. Subsidy reforms need clear goals, co-design, transparency, and fair implementation. An agreement on SDG 14.6 could be a turning point for the oceans and for the well-being of those that depend on the oceans for livelihoods and nutrition. Responsible seafood production will require international cooperation not only at WTO, but among governments, fisher organizations, civil society, and the wider public.